Effect of growth regulators on maturity of fruit and quality of coffee drin (Research, Society and Development, 2019)
This study aimed to obtain more uniform ripening of the fruits harvested by applying growth regulators Ethephon and Mathury™, aimed at improving the quality of coffee drinks. Was used to cultivate Tupi Yellow (IAC 5162), planted in December 2008. The experimental design was a randomized blocks, being employed five treatments: T1 Application Mathury™ to 113 days prior to collection (DAC); T2 Application Mathury™ after 85 DAC; T3 Application Mathury™ after 57 DAC; T4 Ethephon application when the plants were 30% of cherry fruit and T5- Control (without applications). After sorting the fruit maturation percentage, we selected those who were classified as cherry; these were dried and submitted to analysis: selection by size; classification by type of defects; sugars; solid soluble; electrical conductivity; potassium leaching; titratable acidity; ether extract; pH and sensory analysis. There was a significant difference in the ripening of fruits, noting an increase of 57% the percentage of cherry fruit and 89% reduction of fruit goes through when applied Ethephon. While there have been differences in the percentage of fruit maturation and the physical-chemical analysis, it is concluded that such differences did not influence the coffee beverage quality as it achieved the same standard classification panel test.